Statistical Methods in the Analysis of Pollution Impacts on Human Health - ROSSINSKAYA, Marina V.; ROKOTYANSKAYA, Violetta V.; MEDOVY, Valery V.; IVANOVA, Ekaterina V.; SHADUYEVA, Elvira Ch. (Journal of Advanced Research in Law and Economics; Vol 9 No 4 (2018): JARLE Volume IX Issue 4(34) Summer 2018, 2018)
The problems of sustainable development of socio-ecological systems are deeply related to the safety of the society's functioning, which depends on many factors and requires a systematic evaluation and special approaches to determine all their aspects. The article discusses a wide range of actual problems of monitoring and forecasting in the system of assessing the ecological, social and economic security of a region, and analyses the rationale of statistical analysis methods. But, it is has to be noted that for a number of important indicators there is no reliable statistical information, and this fact negatively affects the results of the study. A complex cluster analysis of the impact of human economic activity on the environment and public health has been carried out on the example of the Southern Federal District of the Russian Federation.